L'obligation de bonne foi du créancier face à l'entreprise en difficulté en droit québécois et canadien - Demers, Robert (Les Cahiers de droit, 1981)
This article deals with the creditor's duty of good faith towards a business in financial difficulties. While the common law rules have established over the years a duty of bona fides towards the debtor, our provincial courts were wary of such innovations and, as a general rule, had refused to consider any major changes in their policy. Recent pronouncements, however, indicate a more equitable interpretation of the creditor-debtor relationship and a consciousness of the role of the judiciary in difficult economic situations.